Echa doktryny political juriprudence w polskiej debacie o podstawach rządów prawa (2015-2025) - Dobrzeniecki, Karol (PRAWO i WIĘŹ, 2026)
The objective of this paper is to demonstrate how the ongoing debate in Poland concerning the foundations of the rule of law within the context of the constitutional crisis reveals motifs that directly correspond to the doctrine known as Martin Shapiro’s political jurisprudence. The paper outlines the core tenets of this theoretical current, as well as its acknowledegment of the concept of the political as a defining characteristic of political lawyers. The disputes among Polish legal scholars, which took place between 2015 and 2025, pertained to issues such as the political engagement of judges and the dynamics of power within the structure of the judicial branch. Many of the arguments advanced and solutions put forward represent a departure from the premises of legal positivism, a rejection of the methodological thesis regarding the autonomous character of the legal system, and a confirmation of the inextricable link between law and politics.